Use of Poultry Litter-Based Fertilizers in Calcareous Soil: Effects on Corn Growth and Selected Properties - Mohamed El-Mahrouky; Fahad N. Al-Barakah; Jeff. J. Schoenau; Ibrahim Ahmed; Khaled D. Alotaibi; Shah Fahad (Applied and Environmental Soil Science)
Continual rise in poultry production to meet increasing food demand also generates a huge amount of waste. This accumulating waste can lead to soil, water, and air contamination if not properly managed. Efficient management and utilization of poultry waste is one of the key steps toward ensuring agricultural and environmental sustainability. Direct application of fresh poultry litter (PL) to soil is a potential option; however, its high moisture content, unpleasant odor, and high nutrient loss potential, especially under arid conditions, can limit this option. Conversion of PL to more stable fertilizers may be a more sustainable practice for its utilization in arid soil. Therefore, a greenhouse study was conducted to evaluate the effect of organic fertilizers derived from PL on corn growth and nutrition in a calcareous soil. The experimental treatments included: raw poultry litter (RPL), composted PL (CPL), pelletized CPL (PCPL), and PL converted to biochar (PLBC) in addition to a control. These treatments were applied at rates of 5, 10, and 15 t·ha−1, except for the control, which received only a single dose of recommended mineral fertilizers. The plant growth response to treatments varied according to the type of fertilizer and rate of application. The PLBC added at 10 and 15 t·ha−1 showed significantly higher plant height, shoot weight, and root dry weight, followed by the same rates of CPL compared to other treatments. Relative to the control, PLBC increased plant height by 0.3%, 18.6%, and 21.1% for the application rates of 5, 10, and 15 t·ha−1, respectively. The shoot content of N and P did not statistically differ among all treatments, whereas the K content was significantly higher in PLBC when applied at 15 t·ha−1. Calcium concentration was also increased in the corn, with PLBC producing a 9.7%, 9.7%, and 16.7% increase, respectively, over the control, for the application rates of 5, 10, and 15 t·ha−1, respectively. The PLBC applied at 15 t·ha−1 significantly increased soil nitrate (58 mg·kg−1), available P (49 mg·kg−1), available K (189 mg·kg−1), and organic matter (1.96%). The PLBC can improve several soil properties and create favorable conditions for plant growth, and this may explain its best performance in the current study. Overall, poultry-derived organic fertilizers have greater potential for improving corn growth and soil conditions, compared to RPL. Further long-term studies in the field are required to validate the current findings.